Examining How Integrated Smart Logistics Ecosystems Enhance E-Commerce Efficiency in the UAE Retail Sector - Kazim, Ahmad Mohammad Jaffar Hussain; Baskaran, Kamaladevi (Journal of Posthumanism, 2025)
This study examines how integrated smart logistics ecosystems enhance e-commerce efficiency in the UAE’s fast-growing retail sector. As digital transformation and evolving consumer expectations reshape the market, companies are turning to smart logistics solutions, combining advanced technologies, last-mile delivery optimization, and collaborative frameworks to improve operational performance. Adopting a quantitative methodology within a positivist and deductive approach, the research analysed data using SPSS through descriptive and correlation techniques. Findings indicate that while AI, IoT, and other smart technologies contribute to logistics efficiency, their direct impact on e-commerce performance is significantly increased when aligned with strong stakeholder collaboration. Collaboration within the supply chain emerged as the most influential factor, enhancing both logistics strategy effectiveness and sales outcomes. The study concludes that logistics technologies must be embedded in a cooperative, integrated ecosystem to realize meaningful improvements. It contributes to e-commerce and logistics by integrating Resource-Based and Supply Chain Integration within a smart logistics framework.